Efficiency Improvement of Solar Cell - Shaikh Sajid Shaikh Dawal, Shah Faisal, Muqueem M khan, Momin Shahbaz Akhter, Shaikh Shahbaz (International Journal of Advanced Science and Technology, 2020)
PV cell converts solar radiation directly into electricity. Solar energy is great significance or value. energies within the future., Recently, there has been an enormous technology to increase the electrical efficiency of solar cell. When solar cell absorbs solar radiation then its temperature increases, that causes a decrease in its efficiency. Temperature of PV cell can be partially reduced by applying a cooling system on PV cell with fluid circulation around the PV cell. Such system is known as photovoltaic/thermal collector (PV/T) or hybrid (PV/T). The objective of this paper is to design a cooling system to the solar cell in order to increase its efficiency and also to extract the heat energy from cell. A hybrid solar system which generates both electricity and heat energy simultaneously is studied in the paper. This hybrid solar system consists of PV cells attached to an absorber plate with fins attached at the other side of the absorber surface of the cell..Keywords: Plate PV/T Collector, Solar Irradiance, Electrical Efficiency, Electrical Power.